Targeting oral cancer stemness and chemoresistance by isoliquiritigenin-mediated GRP78 regulation - Hu, Fang-Wei; Yu, Cheng-Chia; Hsieh, Pei-Ling; Liao, Yi-Wen; Lu, Ming-Yi; Chu, Pei-Ming (Oncotarget, 2017)
Cancer stem cells (CSCs) are cells that drive tumorigenesis, contributing to metastasis and cancer recurrence as well as resistance to chemotherapy of oral squamous cell carcinomas (OSCC). Therefore, approaches to target CSCs become the subject of intense research for cancer therapy. In this study, we demonstrated that isoliquiritigenin, a chalcone-type flavonoid isolated from licorice root, exhibited more toxicity in oral cancer stem cells (OSCC-CSCs) compared to normal cells. Treatment of isoliquiritigenin not only inhibited the self-renewal ability but also reduced the expression of CSC markers, including the ALDH1 and CD44. In addition, the capacities of OSCC-CSCs to invade, metastasize and grow into a colony were suppressed by isoliquiritigenin. Most importantly, we showed that isoliquiritigenin potentiated chemotherapy along with downregulated expression of an ABC transporter that is associated with drug resistance, ABCG2. Moreover, a combination of isoliquiritigenin and Cisplatin significantly repressed the invasion and colony formation abilities of OSCC-CSCs. Our results suggested that administration of isoliquiritigenin reduced the protein expression of mRNA and membrane GRP78, a critical mediator of tumor biology. Overexpression of GRP78 reversed the inhibitory effect of isoliquiritigenin on OSCC-CSCs. Furthermore, isoliquiritigenin retarded the tumor growth in nude mice bearing OSCC xenografts. Taken together, these findings showed that isoliquiritigenin is an effective natural compound that can serve as an adjunct to chemotherapy for OSCC.